Comparison of clinical and patient-reported outcomes of three procedures for recurrent anterior shoulder instability: arthroscopic Bankart repair, capsular shift, and open Latarjet - Yingjie Xu; Kailun Wu; Qianli Ma; Lei Zhang; Yong Zhang; Wu Xu; Jiong Jiong Guo (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Best surgical of recurrent anterior shoulder instability remained controversial. We knew little about the superiority and choice between traditional open and modern arthroscopic techniques. We hypothesized that outcomes of all patients will be similar regardless of surgical technique. Methods A retrospective case-cohort analysis of 168 patients who had recurrent anterior shoulder instability was conducted from September 2010 to December 2013. All cases (mean age 30.8 [range 18–50] years) were performed with arthroscopic Bankart repair (33 males/20 females), open Latarjet (34 males/18 females), and capsular shift (31 males/14 females). The average follow-up was 67.6 months (range 60–72). The shoulder instability index score (ISIS) was more than 3 with an average of 6.4. Results All treatments proved to be effective in improving shoulder functional status and reducing symptoms, while Latarjet had an advantage over subjective perception. The Rowe scores in arthroscopic Bankart, open Latarjet, and capsular shift group were 92.3 ± 1.5, 96.2 ± 2.1, and 93.2 ± 2.3, respectively, with significant difference. There was no significant difference in other functional outcomes. However, the Latarjet group in subjective results (subjective shoulder value (SSV) and subjective shoulder value for sport practice (SSV Sport)) was superior to the others (P < 0.05). There were two relapsed cases in arthroscopic Bankart and capsular shift group, respectively, and no recurrence in open Latarjet group. Conclusion Arthroscopic Bankart repair has the advantage of mini-invasion and rapid recovery. Capsular shift offers stabilizing of inferior or multidirectional type, especially for little bone defect. Latarjet was more effective in reducing recurrence with higher stability. Level of evidence Therapeutic level III